Intellectual property policy and academic patenting in Malaysia: challenges and prospects - Azmi, Ida Madieha (UPM Press, 2014)
The Malaysian government has identified innovation as the main economic driver in the transition to a high income nation in 2020. In Malaysia, the public universities and public research institutes have been instrumental in the creation of intellectual property for the country. This paper begins with a foray into the rise of academic patenting in Malaysia by looking at patent statistics filed by academic institutions and government research institutes. It then examines two national policy instruments that have been formulated by the government to encourage technology transfer to the industry i.e. the Government Circular on the Management of Intellectual Property owned by the Government and the Distribution of Royalties 1999and Intellectual Property Commercialisation Policy for Research and Development (R&D) Projects Funded by the Government of Malaysia. To examine the wisdom of these two policy instruments, their provisions are compared to the US Bayh-Dole Act 1980. The paper continues to examine some of the key US court decisions on the interpretation of the Bayh-Dole Act. Finally, the paper explores the position of institutional intellectual property polices in determining IP ownership disputes between the university employer and the academic employee. For this purpose, a comparable Australian case in which a university IP policy was scrutinized is discussed. This is done in order to have a better understanding of the legal challenges that might face any claims of IP ownership by academic institutions. The paper ends by suggesting that academic institutions in Malaysia will continue to play a big role in churning intellectual property for the country if the current policy stand is to be maintained.